Self-reported voice disorders of teachers and indoor air quality in schools: a cross-sectional study in Finland - Vertanen-Greis Hanna; Löyttyniemi Eliisa; Uitti Jukka; Putus Tuula (TAYLOR & FRANCIS LTD, 2025)
Objective We aimed to study the association between self-reported voice disorders among teachers and indoor air quality in school buildings. Methods We performed a questionnaire study of 538 Finnish teachers working in 67 school buildings utilizing both perceived and technical evaluations; the agreement between these two assessments was also studied. The technical assessment was provided by technical experts. Results Teachers with voice disorders reported significantly more complaints from indoor air than those without voice disorders. The results also indicated a possible connection between the technical assessment and voice disorders. After adjustment for sex, stress and asthma, the prevalence of voice disorders was 47% higher in teachers working in renovated buildings compared to those working in the non-problem buildings (aRR1.47; CI 95% 1.11-1.95). The prevalence of voice disorders was 28% higher among teachers working in buildings with problems compared to those working in non-problem buildings (aRR 1.28; 95% CI 0.99-1.64). Discussion In our study, poor perceived indoor air was significantly associated with self-reported voice disorders in teachers and there was an agreement between the perceived and technical assessments. Our results also indicated a possible connection between the technical assessment and voice disorders. Our results imply the need for longitudinal research with technical assessment to study the effect of renovation on voice disorders.